2022
DOI: 10.1038/s41598-022-08608-z
|View full text |Cite
|
Sign up to set email alerts
|

Validation of a CE-IVD, urine exosomal RNA expression assay for risk assessment of prostate cancer prior to biopsy

Abstract: Improved risk stratification of patients suspected of prostate cancer prior to biopsy continues to be an unmet clinical need. ExoDx Prostate (IntelliScore) “EPI” is a non-invasive urine test utilizing RNA from exosomes to provide a risk score that correlates with the likelihood of finding high grade prostate cancer at biopsy. Here, we present the results from a prospective clinical validation study of EPI-CE, a CE-marked in-vitro diagnostic (IVD) assay, specifically developed for use in European clinical labor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
13
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 19 publications
(13 citation statements)
references
References 14 publications
0
13
0
Order By: Relevance
“…In addition, gene expression signature from urine exosomes also demonstrated a reliable clinically relevant predictive role (NPV 91.0%) in the decision making of patients with negative histological results [64]. Interestingly, the EPI urine biomarker was significantly associated with low-risk disease, making it a good test to select patients for AS [101].…”
Section: Ctrnamentioning
confidence: 96%
“…In addition, gene expression signature from urine exosomes also demonstrated a reliable clinically relevant predictive role (NPV 91.0%) in the decision making of patients with negative histological results [64]. Interestingly, the EPI urine biomarker was significantly associated with low-risk disease, making it a good test to select patients for AS [101].…”
Section: Ctrnamentioning
confidence: 96%
“…Publications with the highest level of evidence were selected for review. This yielded 60 articles for which full text evaluation was performed and included in the final review 12–71 . A flow diagram of the article evaluation process is shown in Figure 1.…”
Section: Methodsmentioning
confidence: 99%
“…In a small cohort, Pang et al 70 showed that size-exclusion chromatography-based methods provided purer populations of EVs compared with precipitation methods in blood for PCa diagnosis. Notably, the ExoDx Prostate (IntelliScore) test based on EV detection of long noncoding and gene fusion RNAs in urine has been shown to aid detection of high-risk disease 66,67 Likewise, when performed before repeat biopsies in men with previous negative biopsies, the ExoDx test could predict high-risk disease in the repeat biopsy setting 64 . In other assays, plasma EVs positive for the protein STEAP1 had significant biomarker potential for detection/diagnosis but carried little prognostic information 69 .…”
Section: Evidence Synthesismentioning
confidence: 99%
“…The combination of ADSV and TGM4 can be used to distinguish benign tumors from malignant prostate tumors. The ExoDx Prostate IntelliScore from Exosome Diagnostics, which is based on the detection of ERG, PCA3, and SPDEF RNA in urinary exosomes, can be used to distinguish high-grade PC from low-grade PC and benign disease, and the combination of five proteins (i.e., CD63, GLPK5, SPHM, PSA, and PAPP) able to serve a similar purpose [ 168 , 170 , 171 ]. Furthermore, the semen exosome-based PSA/miR-142-3p/miR-142-5p/miR-223-3p model has shown potential for improving PC diagnostic/prognostic efficiency [ 169 ].…”
Section: Prospective Applications Of Exosomes In Pc Diagnostics and T...mentioning
confidence: 99%